Design and Characterization of Nanopore- Assisted Weakly-Coupled Few-Mode Fiber for Simpler MIMO Space Division Multiplexing - Yuheng Xie; Li Pei; Jingjing Zheng; Tigang Ning; Jing Li; Bo Ai; Ruisi He (IEEE Access, 2020)
We report on a novel weakly-coupled 6-LP-mode fiber that features a nanopore-assisted step-index core with double-cladding profile. The purpose of this fiber design is to alleviate modes coupling and bend sensitivity, thus simplifies the multiple-input multiple-output (MIMO) process and the environmental requirements in which the fiber is used. Through numerical simulations, we show that the minimum effective index difference (Δfleff) of larger than 1.8*10-3 among all LP-mode over C and L band can be achieved by a simple nanopore with 170 nm radius in the center of the core. Furthermore, the dependences of both bending loss and chromatic dispersion on fiber structures are investigated by the finite element method (FEM) to show the good broadband performance. The proposed fiber targets applications in simpler MIMO space division multiplexing (SDM) systems such as data center and short-reach large-capacity transmission.